EFFECT OF INSTRUCTIONAL SCAFFOLDING ON ACHIEVEMENT IN BIOLOGY BY SECONDARY SCHOOL STUDENTS’ WITH DIFFERENT COGNITIVE STYLES IN AWKA EDUCATION ZONE (UNIZIK Journal of STM Education, 2019)
The study investigated the effect of instructional scaffolding on achievement in biology by secondary school students with different cognitive styles in Awka Education Zone. Five research questions guided the study and six hypotheses were tested in the study at 0.05 level of significance. The study adopted quasi-experimental design specifically, the pre-test post-test control group non-equivalent control group design. The population of the study consisted of 3,065 senior secondary school two (SS2) students offering biology in Awka Education Zone. Multistage sampling procedure was used to select a sample size of 108 students involved in the study. The instruments used for data collection were Biology Achievement Test (BAT) and Group Embedded Figure Test (GEFT). The BAT was validated by experts in Department of Science Education and Education Foundation and one experienced biology teacher. BAT reliability was established using Kudder Richardson 20 which yielded reliability coefficient of 0.80. Students in the experimental group were taught using instructional scaffolding while those in the control group were taught using conventional method. Data relating to the research questions was analysed using mean and the hypotheses were analysed using Analysis of Covariance. The findings of the study showed that instructional scaffolding improved the achievement of field dependent and field independent students. The study also found out that the use of instructional scaffolding enhanced the achievement of field independent students more than those that of field dependent. Based on the findings, it was recommended among others that Science Teachers Association of Nigeria should organize seminars and workshops to train biology teachers on the use of instructional scaffolding.
Keywords: Scaffolding; biology; achievement; cognitive styles